RTHP-34. IMPROVED SURVIVAL IN CNS LYMPHOMA WITH SALVAGE LOW-DOSE WHOLE-BRAIN RADIOTHERAPY WITH FOCAL BOOST AND CONCURRENT TEMOZOLOMIDE - Selwa, Katherine (Neuro Oncol, 2019)
OBJECTIVE: There is no standard salvage radiotherapy (RT) regimen, nor a consensus on the concurrent chemotherapy use in CNS lymphoma. We assessed the efficacy of low-dose whole-brain radiotherapy (WBRT) with focal-boost to the area of disease and concurrent temozolomide for the salvage treatment of CNS lymphoma. METHODS: A single center retrospective study of CNS lymphoma patients seen between 01/2004 and 02/2019. The inclusion criteria were: diagnosis of CNS lymphoma, age > 18 years at diagnosis, radiation treatment to the brain, and formulation of plan at University of Michigan with at least one follow-up. Overall survival (OS) was determined by Kaplan Meier method. RESULTS: Out of 93 patients (median age 58, 45% female), 73% were diagnosed with primary CNS lymphoma (n=68), and the remainder with secondary CNS lymphoma. Radiation modalities were WBRT alone (n=52), low-dose WBRT + focal boost (n=33) and focal RT alone (n=8). Twenty-six patients (28%) received concurrent temozolomide with radiation. Those who received WBRT+boost achieved complete response at a significantly higher rate than those who received WBRT alone (36% vs 17% respectively, p=0.047). The median OS among all groups was 45 months. There was a significant improvement in OS in patients receiving low-dose WBRT+boost compared to WBRT alone (median 65 vs 14 months respectively, p=0.016). OS was significantly longer in patients who received concurrent temozolomide than in those who did not (median 86 vs 23 months respectively, p=0.0287). CONCLUSIONS: In CNS lymphoma salvage RT, a longer survival was observed with low-dose WBRT with focal-boost compared to WBRT alone, as well as with concurrent temozolomide. This result is limited by the selection bias to each of the treatment groups; however, the low-dose WBRT with focal-boost and concurrent temozolomide is a useful salvage alternative to standard WBRT as it may reduce long-term neurocognitive toxicity.